Diagnostic accuracy of methylated SEPT9 for primary liver cancer: a systematic review and meta-analysis - Jin, Danwen; Qian, Liyong; Chen, Jiayao; Yu, Ze; Dong, Jinliang (Frontiers in Endocrinology, 2025)
BackgroundPrimary live cancer (PLC), including hepatocellular carcinoma (HCC) and intrahepatic cholangiocarcinoma (ICC). This meta-analysis was conducted to evaluate the diagnostic efficacy of blood methylated septin 9 gene (mSEPT9) for PLC and to analyze its performance across various subgroups.MethodsWe conducted a comprehensive search across PubMed, the Cochrane Library, Embase, and China National Knowledge Infrastructure (CNKI), covering research up to May 10, 2024. The pooled sensitivity, specificity, diagnostic odds ratios, and area under the summary receiver operating characteristic (AUC) were calculated for the diagnostic performance of mSEPT9 for PLC. The quality of the studies was assessed using the QUADAS-2 tool, and the meta-analysis was performed using Stata16.0 software.ResultsTen articles with 2,182 participants were included in the meta-analysis. The pooled sensitivity of mSEPT9 for detecting primary liver cancer was 0.51 (95% confidence interval [CI]: 0.37-0.65), and the pooled specificity was 0.93 (95% CI: 0.78-0.98). The pooled diagnostic odds ratio was 13 (95% CI: -58), and the area under the Summary Receiver Operator Characteristic Curve was 0.75 (95% CI: 0.71-0.79). Subgroup analyses showed that ICC, case-control studies, qPCR and Asian populations had higher specificities (0.99 [95% CI: 0.97–1.00], 0.93 [95% CI: 0.91-0.95], 0.90 [95% CI: 0.88-0.92] and 0.94 [95% CI: 0.92-0.96], respectively) and diagnostic odds ratios (62.04 [95% CI: 6.53-589.53], 17.62 [95% CI: 4.03-76.99], 13.03 [95% CI: 2.01-84.63] and 14.19 [95% CI: 2.42-83.11], respectively) compared to hepatocellular carcinoma, cohort Study, and Euramerican populations.ConclusionsThis study confirmed that mSEPT9 in blood has high specificity and moderate sensitivity for detecting primary liver cancer. The diagnostic performance of mSEPT9 varied across different subgroups, limiting its use as an independent screening tool and necessitating its use in conjunction with other methods for confirmatory diagnostics.Systematic review registrationhttps://www.crd.york.ac.uk/prospero/, identifier CRD42024549669.